2011
DOI: 10.1093/ajae/aar044
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Returns to U.S. Public Agricultural Research

Abstract: We use newly constructed state-specific data to explore the implications of common modeling choices for measures of research returns. Our results indicate that state-to-state spillover effects are important, that the R&D lag is longer than many studies have allowed, and that misspecification can give rise to significant biases. Across states, the average of the own-state benefit-cost ratios is 21:1; or 32:1 when the spillover benefits to other states are included. These ratios correspond to real internal rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 23 publications
5
96
1
Order By: Relevance
“…The average social rate of return ranged from 14.35% in Model 2 to 39.56% in Model 1. These IRR rates are lower than the ones in [15] and [16] 12 . Table 9 reports the rates of return by production region.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…The average social rate of return ranged from 14.35% in Model 2 to 39.56% in Model 1. These IRR rates are lower than the ones in [15] and [16] 12 . Table 9 reports the rates of return by production region.…”
Section: Resultscontrasting
confidence: 53%
“…where f indicates the state that makes the investment in public R & D, g indexes the states hypothesized to benefit from the spillovers from the research investment in state f, and q indicates the total number of states that benefit from the 3 Most studies have calculated internal rates of return, although the study by Alston et al [15] has also calculated a modified internal rate of return [32]. For a detailed discussion of the IRR rule in investment projects see Chapter 8 in Brealey, Myers, and Marcus [33].…”
Section: Internal Rate Of Return To Agricultural Researchmentioning
confidence: 99%
“…We measure the R&D expenditures as expenditures to agricultural sciences (Frascati manual, OECD 2002) which comprise both public and private spending. Our methodological approach follows Thirtle et al (2008) and Alston et al (2011), who analyzed the R&D effects on agriculture in the UK and the USA, respectively. To our knowledge, there has not been any recent study performed on the countries in the Central and Eastern Europe, which is probably due to the lack of a consistent time series.…”
Section: Description Of the Methodological Approach Applied In The Papermentioning
confidence: 99%
“…They do not allow for lags of 50 or more years, as in Alston et al (2011) or Thirtle et al (2008. This limits our analysis; however, we believe that the transfer of knowledge could accelerate in the focus period due to several factors: in the 1970s and 1980s agriculture was one of the few sectors exhibiting substantial dynamics and growing income.…”
Section: Time Series Analysismentioning
confidence: 99%
“…Wang (2014) indicates that an increase in extension FTEs per number of farms or square miles can increase the benefits of public research and improve productivity by reducing costs. Alston et al (2011) reported that extension accounted for 7.3% of annual productivity growth for the period 1949 to 2002. In order to feed our growing population, agriculture needs a constant influx of new research, development of ideas, and a viable extension system for delivery and transfer of that knowledge and technology to clients.…”
Section: Discussionmentioning
confidence: 99%